The Level of Moral Identity among Adolescent Students according to Gender and Age - Melhem, Mohammad Amein; Aljarrah, Abedelnaser Diab; Alrabee, Faisal Khalil (Dirasat: Educational Sciences, 2020)
The study aims to examine the level of moral identity among adolescent students at the Second Educational Directorate of Irbid according to their gender and age. The sample of the study included (398) male and female adolescent students selected using stratified sampling procedures. To achieve the objectives of the study, a moral identity scale developed by Acquino and Reed (2002) was used. Validity and reliability were established for the scale. The results of the study indicated that the total construct of moral identity and the individual construct of internalization were high while it was moderate on the individual construct of symbolism. The total level of moral identity and the individual construct of symbolism was higher among females. It was also found that adolescent students in the age group (12- less than 16) reported higher scores on the total moral identity level and the individual construct of internalization compared to those in the age group (16-18). There were no statistically significant differences at the level (α=0.05) between the mean scores of adolescent students in the total construct of moral identity and the individual construct of symbolism and internalization due to the interaction of gender and age group.